RESEARCH ON PLUG-IN FILLET WELD FLAW DETECTING BY USING FLEXIBLE PHASED ARRAY TECHNIQUE - QIAN ShengJie; HUANG HuanDong; SHEN ChengYe; WANG Du; HUANG Hui; CHEN DingYue (Jixie qiangdu)
According to the common structure characteristics of the plug-in fillet weld, a new weld defect detecting method was presented in this paper. The flexible phased array probe was inserted into the internal surface of the tube under water immersion during the detection process. The beam focusing model of convex flexible phased array was theoretically analyzed. Meanwhile, the acoustic focus beam with CIVA software were simulated. The typical flaws were added to the model of plug-in fillet weld, and defect response were obtained. The sample of the plug-in fillet weld with artificial flaws is manufactured, the system was calibrated in the laboratory. The experiment results indicated that this technique can successfully detect the typical flaws of crack, slag and porosity. Finally, the technique was applied to the manufacture quality inspection of the products, one incomplete penetration and one porosity were detected. The detecting system can effectively ensure the general welding flaws of the product were detected.